The role of human factors in paramedics’ clinical judgement – A modified Delphi study - Anna Poranen; Anne Kouvonen; Hilla Nordquist (PLoS ONE, 2025)
Objective In emergency medical services (EMS), work environments and circumstances are variable and make clinical judgement challenging. Little is known about the human factors that can affect paramedics’ clinical judgement in different situations. The aim of this study was to identify the key human factors that can affect paramedics’ clinical judgement during EMS missions, according to paramedic experts. Methods A three-round modified Delphi study was conducted in 2024. Advanced level paramedics with at least five years of experience in EMS across Finland were included in the study. In the first two rounds, experts evaluated statements using seven- and five-point Likert scales. In Round 3, experts selected the five most significant human factors affecting paramedics’ clinical judgement and describe related situations. The consensus level was set at ≥ 75%, and open-ended responses were analysed using thematic analysis. Results Forty-seven experts participated in Round 1 and the response rates for Rounds 2 and 3 were 91% and 58%, respectively. After Round 1,16 statements were removed, 20 new statements were introduced, and four original statements were revised for Round 2. As consensus was not reached in the first two rounds, the analysis approach was modified to report medians and interquartile ranges (IQR). The experts identified 13 key human factors (IQR ≤ 1), with the four most significant being: 1) Unsafe locations involving a perceived risk to one’s own and/or colleagues’ work safety; 2) One’s own attitude towards work tasks; 3) Support received from a physician when carrying out the mission, and 4) One’s own and one’s work partner’s problem-solving ability in relation to the situation at the scene. Conclusions The present study found consensus on the four most significant human factors affecting paramedics’ clinical judgement. Organisations need to provide adequate resources for situations involving occupational safety risks and provide support for paramedics’ mental wellbeing.